2014
DOI: 10.1038/ncomms4602
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale reorganization of the somatosensory cortex following spinal cord injuries is due to brainstem plasticity

Abstract: Adult mammalian brains undergo reorganization following deafferentations due to peripheral nerve, cortical or spinal cord injuries. The largest extent of cortical reorganization is seen in area 3b of the somatosensory cortex of monkeys with chronic transection of the dorsal roots or dorsal columns of the spinal cord. These injuries cause expansion of intact face inputs into the deafferented hand cortex, resulting in a change of representational boundaries by more than 7 mm. Here we show that large-scale reorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
124
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 50 publications
2
124
2
Order By: Relevance
“…First, invading signals from other body regions reflect the unmasking of lateral connections at the level of the cuneate nucleus (Kambi et al, 2014), rather than major structural and functional changes in deafferented cortex. Second, neural activity is evoked in the deafferented cortex during phantom hand "movements" (Makin et al, 2013b;Raffin et al, 2012).…”
Section: The Problem Of Cortical Plasticitymentioning
confidence: 99%
“…First, invading signals from other body regions reflect the unmasking of lateral connections at the level of the cuneate nucleus (Kambi et al, 2014), rather than major structural and functional changes in deafferented cortex. Second, neural activity is evoked in the deafferented cortex during phantom hand "movements" (Makin et al, 2013b;Raffin et al, 2012).…”
Section: The Problem Of Cortical Plasticitymentioning
confidence: 99%
“…After cervical dorsal column section, neurons in the deafferented area 3b become initially unresponsive to stimulation of the hand, but after few weeks the area of cortical activation to spared inputs is greatly expanded, and after few months the deafferented hand cortical area becomes responsive to inputs from the face (Jain et al, 2000, 2008). This cortical reorganization is related to sprouting in the trigeminal-dorsal column complex in the brainstem (Jain et al, 2000; Kambi et al, 2014), and can also be observed at thalamic level (Jain et al, 2008). This reactivation of the deafferented hand cortex by inputs from the face seems more likely to contribute to phantom limb sensations than to functional recovery (Kaas et al, 2008), whereas the recovery of a near-normal cortical hand representation, possibly through alternate spinal afferents, seems to correlate with the recovery of hand use (Qi et al, 2014).…”
Section: Cortical Reorganization Depends On Species (Fig 1)mentioning
confidence: 99%
“…The occurrence of anatomical alterations in the cortex after deafferentation (Florence et al, 1998), in addition to the notion that neocortex is a very plastic structure, led to the view that cortical reorganization of sensory maps after lesions is driven, at least in part, by cortical mechanisms. Recent work published by Kambi et al (2014) contradicts this paradigm. In order to determine the extent to which different sites of somatosensory pathway potentially contribute to cortical plasticity, Kambi and colleagues lesioned the dorsal column in monkeys.…”
mentioning
confidence: 97%
“…Simultaneous recordings from the normal chin and deafferented body representation of S1 demonstrated the expansion of the chin area in animals with dorsal column lesions (Kambi et al, 2014). Based on previous studies, it would be expected that this was due to new corticocortical connections, at least in the vicinity of the face/hand border.…”
mentioning
confidence: 99%